Scapholunate Ligament Reconstruction without Immobilization Is Safe and Leads to Better Functional Results - Kemler, Marius A.; Bootsman, Josette J.; van den Berg, Johan (Journal of Wrist Surgery, 2022)
Background Reconstruction of the scapholunate ligament (SL) is associated with a reduction in range of motion. In this study, we compared SL reconstruction and early mobilization with SL reconstruction and Kirschner wires (K-wire) fixation for 6 weeks.Methods We performed a nonrandomized trial involving patients with an arthroscopically confirmed SL ligament injury. In total, 11 patients were assigned to SL reconstruction with internal brace augmentation and early mobilization and 10 were assigned to standard SL reconstruction and K-wire fixation for 6 weeks before mobilization started. We assessed the range of motion, grip strength, functional status, intensity of pain, global perceived effect, and duration until return to work.Results In both groups, there was one traumatic breakout of the reconstructed ligament and two patients in the control group were lost to follow-up. The 10 patients in the internal brace group had a mean increase in wrist flexion of 1.8 degrees at 1 year compared with a decrease in wrist flexion of 13.4 degrees in the seven patients of the control group. Wrist extension increased by 4.5 degrees in the internal brace group and decreased by 4.5 degrees in the control group. In addition, the internal brace group scored 6.1 (much improved) for the global perceived effect and the control group 4.7 (slightly improved), and treatment without immobilization resulted in an earlier return to work (35.1 vs. 73.6 days).Conclusions In SL reconstruction, internal brace augmentation and early mobilization result in improved wrist flexion and extension, higher satisfaction, and earlier return to work.
Keywords: immobilization; internal brace; scapholunate ligament